Spatial and time distribution of the flash rate over tropical Africa - Burgesser, Rodrigo Exequiel (2013)
The lightning flash rate over tropical Africa was analyzed using lightning data of two independent lightning detection systems, the World Wide Lightning Location Network and the Lightning Imaging Sensor. Spatial and time distributions of lightning activity were studied using different spatial and temporal scales. Results show a very localized high-lightning activity center on the west side of the Albertine Rift Mountain, located east of the Congo Basin, and substantial lightning activity in the center of the region. Both centers show low variations on the lightning activity throughout the year and a marked diurnal cycle with a maximum lightning activity in the local afternoon. A secondary lightning activity center was found over Lake Victoria, which has an annual variation similar to that of the Congo Basin lightning activity centers but does not show a marked diurnal cycle. The lightning activities observed seem to be strongly influenced by topography and are in agreement with the small temperature ranges and with the rainfall observed in the region.